Pengembangan e-LKPD Berbasis Live Worksheet Pada Muatan PPKn Siswa Kelas 4 SD Negeri 2 Karanganyar Kebumen - Pratomo, Wachid; Nadziroh; Chairiyah; Putri, Yunindra Khairunnisa (CV. Kurnia Grup, 2023)
The aim of this research is to describe: 1) development of live worksheet-based e-LKPD on PPKn content for grade 4 students at SD Negeri 2 Karanganyar Kebumen; 2) the feasibility of developing Live Worksheet-based e-LKPD for PPKn content for grade 4 students at SD Negeri 2 Karanganyar, Kebumen. This type of research is Development (R&D) with the ADDIE model. Data collection techniques use observation, questionnaires and interviews. Data is processed through quantitative and qualitative analysis. The results show that the development of Live Worksheet-Based e-LKPD Teaching Materials for Class 4 PPKn Content at SD Negeri 2 Karanganyar, Kebumen produced teaching material media in the form of Live Worksheet-Based E-LKPD. Media experts assess the feasibility of 96.55% with the criteria